Chemokines as Drivers of the Autoimmune Destruction in Type 1 Diabetes: Opportunity for Therapeutic Intervention in Consideration of an Optimal Treatment Schedule - Christen, Urs; Kimmel, Ruta (Frontiers in Endocrinology, 2020)
Type 1 diabetes (T1D) is mainly precipitated by the destruction of insulin-producing β-cells in the pancreatic islets of Langerhans by autoaggressive T cells. The etiology of the disease is still not clear, but besides genetic predisposition the exposure to environmental triggers seems to play a major role. Virus infection of islets has been demonstrated in biopsies of T1D patients, but there is still no firm proof that such an infection indeed results in islet-specific autoimmunity. However, virus infection results in a local inflammation with expression of inflammatory factors, such as cytokines and chemokines that attract and activate immune cells, including potential autoreactive T cells. Many chemokines have been found to be elevated in the serum and expressed by islet cells of T1D patients. In mouse models it has been demonstrated that β-cells express chemokines involved in the initial recruitment of immune cells to the islets. The bulk load of chemokines is however released by the infiltrating immune cells that also express multiple chemokine receptors. The result is a mutual attraction of antigen-presenting cells and effector immune cells in the local islet microenvironment. Although there is a considerable redundancy within the chemokine ligand-receptor network, a few chemokines, such as CXCL10, seem to play a key role in the T1D pathogenesis. Studies with neutralizing antibodies and investigations in chemokine-deficient mice demonstrated that interfering with certain chemokine ligand-receptor axes might also ameliorate human T1D. However, one important aspect of such a treatment is the time of administration. Blockade of the recruitment of immune cells to the site of autoimmune destruction might not be effective when the disease process is already ongoing. By that time autoaggressive cells have already arrived in the islet microenvironment and a blockade of migration might even hold them in place leading to accelerated destruction. Thus, an anti-chemokine therapy makes most sense in situations where the cells have not yet migrated to the islets. Such situations include treatment of patients at risk already carrying islet-antigen autoantibodies but are not yet diabetic, islet transplantation recipients, and patients that have undergone a T cell reset as occurring after anti-CD3 antibody treatment.